Decoding the Transcriptional Response to Ischemic Stroke in Young and Aged Mouse Brain - Androvic, Peter; Kirdajova, Denisa; Tureckova, Jana; Zucha, Daniel; Rohlova, Eva; Abaffy, Pavel; Kriska, Jan; Valny, Martin; Anderova, Miroslava; Kubista, Mikael; Valihrach, Lukas (Cell reports, 2020)
Ischemic stroke is a well-recognized disease of aging, yet it is unclear how the age-dependent vulnerability occurs and what are the underlying mechanisms. To address these issues, we perform a comprehensive RNA-seq analysis of aging, ischemic stroke, and their interaction in 3- and 18-month-old mice. We assess differential gene expression across injury status and age, estimate cell type proportion changes, assay the results against a range of transcriptional signatures from the literature, and perform unsupervised co-expression analysis, identifying modules of genes with varying response to injury. We uncover downregulation of axonal and synaptic maintenance genetic program, and increased activation of type I interferon (IFN-I) signaling following stroke in aged mice. Together, these results paint a picture of ischemic stroke as a complex age-related disease and provide insights into interaction of aging and stroke on cellular and molecular level.
Keywords: ischemická cévní mozková příhoda; gene expression; interferon; ischemie mozku; WGCNA; stárnutí; axon; Animals; stroke; synapse; Mice; cerebral ischemia; Aging; modely nemocí na zvířatech; Brain Ischemia; aging; Reperfusion Injury; mozek; zvířata; reperfuzní poškození; Ischemic Stroke; Brain; Disease Models, Animal; parvalbumin; RNA-seq; myši